Applied research of training session RPE and blood lactic acid of elite woman wrestlers before competitions - Tang, B. (Exercise Biochemistry Review, 2018)
Objective By testing and analyzing the training session RPE, blood lactic acid, urine protein, urine specific gravity and urine pH value of elite woman wrestlers, investigated variation and score differences of the elite woman wrestlers ' five indicators during the four weeks before the elite woman wrestlers championship, to provide a reference for scientific training.